Structural basis for activation of plasma-membrane Ca2+-ATPase by calmodulin. (December 2018) - Nitsche, Julius; Josts, Inokentijs; Heidemann, Johannes; Mertens, Haydyn; Maric, Selma; Moulin, Martine; Haertlein, Michael; Busch, Sebastian; Forsyth, V.; Svergun, Dmitri; Uetrecht, Charlotte; Tidow, Henning
Abstract Plasma-membrane Ca2+ -ATPases expel Ca2+ from the cytoplasm and are key regulators of Ca2+ homeostasis in eukaryotes. They are autoinhibited under low Ca2+ concentrations. Calmodulin (CaM)-binding to a unique regulatory domain releases the autoinhibition and activates the pump. However, the structural basis for this activation, including the overall structure of this calcium pump and its complex with calmodulin, is unknown. We previously determined the high-resolution structure of calmodulin in complex with the regulatory domain of the plasma-membrane Ca2+ -ATPase ACA8 and revealed a bimodular mechanism of calcium control in eukaryotes. Here we show that activation of ACA8 by CaM involves large conformational changes. Combining advanced modeling of neutron scattering data acquired from stealth nanodiscs and native mass spectrometry with detailed dissection of binding constants, we present a structural model for the full-length ACA8 Ca2+ pump in its calmodulin-activated state illustrating a displacement of the regulatory domain from the core enzyme. Julius Nitsche et al. demonstrate that binding of two calmodulin molecules displaces the regulatory domain of the plasma-membrane Ca2+ -ATPase ACA8 to fully activate this Ca2+ pump by relieving the autoinhibition. This work provides structural evidence for the previously proposed bimodular activation mechanism.